The Beginnings and Endings of Hejaziyat Al-Sharif Al-Radi - Alghanmi, Khalid Hamid Mohammed Nuwaiher (Journal of Arabic Language Sciences and Literature, 2024)
The study examines the significance of the "matali’" (introduction) and "khatma" (conclusion) in Arabic poetry, highlighting their importance in evaluating the quality of poetry. The introduction is seen as a key element in attracting the reader’s attention and showcasing the poet’s skill, while the conclusion is crucial in leaving a lasting impression on the reader and reinforcing the poem’s themes. The study draws on the views of both ancient and modern critics, including Ibn Rashiq and Ibn al-Athir, who emphasize the importance of a well-crafted introduction in establishing the poet’s mastery and engaging the reader. Modern scholars such as Dr. Mustafa Swayf and Dr. Yusuf Husayn Bakkar also stress the role of introduction as a gateway to creative expression and a means of distinguishing between good and poor introductions. Recent studies have underscored the significance of the introduction as an indicator of the poem’s beauty and coherence. The conclusion is also considered a vital component, as it helps solidify the poem’s impact on the reader’s memory. The study proposes an in-depth analysis of the "Hajjajiat" of al-Sharif al-Radi to explore the effects of introductions and conclusions on poetry’s aesthetic and communicative power.